Influence of natural fractures on propagation of hydraulic fractures in tight reservoirs during hydraulic fracturing. (April 2022) - Liu, Yueliang; Zheng, Xianbao; Peng, Xianfeng; Zhang, Yeyu; Chen, Hongde; He, Jianhua
Abstract: Natural fractures in tight reservoirs play an important role in affecting propagation of hydraulic fractures during hydraulic fracturing. In this study, simulated hydraulic fracturing is implemented on nine artificial samples. Within these artificial samples, the pre-existing fractures either showing different dip angles or exhibiting different distances from the simulated wellbore are created to investigate the influence of different types of natural fractures on fracture propagation in tight reservoirs during hydraulic fracturing. Based on the experimental results, propagation of hydraulic fractures varies with the presence of pre-existing fractures having different dip angles during the hydraulic fracturing. Specifically, hydraulic fractures easily go through the pre-existing fractures with high dip angles, while they are hindered by pre-existing fractures with small dip angles. In addition, propagation of hydraulic fractures changes with the distance of pre-existing fractures from simulated wellbore. With a small distance from simulated wellbore, hydraulic fractures are redirected by showing bifurcation from the pre-existing fractures. As the distance increases, hydraulic fractures are less affected by pre-existing fractures. On the contrary, effective stress is the main factor influencing propagation of hydraulic fractures. To validate the laboratory result, microseismic monitoring technology was used detect the influence of natural fractures on propagation of hydraulic fractures in tight reservoirs during a hydraulic fracturing process on Longmaxi Formation in the Fuling area of Sichuan Basin of China. This study is expected to inspire new understanding of the influence of natural fractures on propagation of hydraulic fractures during hydraulic fracturing in tight reservoirs. Highlights: Propagation of hydraulic fractures varies with the pre-existing fractures. Effective stress is the main factor influencing propagation of hydraulic fractures. Microseismic monitoring technology is a good tool investigate the duly fracture propagation.